EVALUASI PROGRAM PENINGKATAN SARANA PRODUKSI PUPUK ORGANIK DI KAWASAN PERDESAAN BERAS ORGANIK KABUPATEN KARANGANYAR - Gunawan Wicaksono; Marsoyo, Agam (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
Rural area development, as mandated by Law number 6 of 2014 concerning Village and Law number 27 of 2007 concerning Spatial Planning, is necessary to accelerate development and community empowerment in rural areas. Hence, The Karanganyar Regency Government compiled an organic rice rural area development plan (RPKP), implemented in 2017-2021. However, a proper program effectiveness evaluation has never been conducted. This study aimed to evaluate the output effectiveness of the organic fertilizer facilities improvement program. This study used a deductive approach with research variables derived from a literature review and supported planning documents, especially the RPKP. Program effectiveness was measured using the output achievement, utilization rate, and cost reduction for activities in the organic fertilizer facilities improvement program in 2017-2019. The observation units and research location consisted of farmer organizations that received the program’s activities in organic rice rural areas, Karanganyar Regency. The results showed that the program was ineffective because entire activities were not running effectively. The number planned output was not fulfilled, the facilities utilization rate was very limited, and most farmer organizations were unable to reduce organic fertilizer’s cost. Factors that affect the program's ineffectiveness are: the preparation of programs and activities in the RPKP has not been discussed with the funding source entity; program content lack clarity in the planning documents and the location of rural areas in the regency spatial planning document (RTRW); coordination and financial support from ministries, regional government, and local village governments; the conditions and planning of farmer organizations receiving the program; and inadequate assistance from the regency government.